2017
DOI: 10.1111/spc3.12340
|View full text |Cite
|
Sign up to set email alerts
|

Racialized physical space as cultural product

Abstract: We argue for incorporating physical space into the psychological study of race. Specifically, we review historical and sociological work explaining how physical space (e.g., houses, rivers, neighborhoods, and nations) has been used to construct race and racial hierarchy, leaving physical space structurally racialized. This structural racialization, we propose, has led people to think of physical space in racial terms, creating mental images of race that include physical space characteristics. We explain how th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 45 publications
(52 reference statements)
1
59
0
Order By: Relevance
“…Social psychologists are increasingly investigating the implications of institution‐level contributors, such as physical spaces, for racial and gender inequality (Bonam, Bergsieker, & Eberhardt, ; Bonam et al ., ; Murphy & Walton, ). Moreover, our recent work has found that too much focus on the individual, rather than systemic, contributors to inequality may have pernicious consequences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social psychologists are increasingly investigating the implications of institution‐level contributors, such as physical spaces, for racial and gender inequality (Bonam, Bergsieker, & Eberhardt, ; Bonam et al ., ; Murphy & Walton, ). Moreover, our recent work has found that too much focus on the individual, rather than systemic, contributors to inequality may have pernicious consequences.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, institutional ‐level contributions to status quo maintenance (cf. Bonam, Taylor, & Yantis, ; Kaiser et al ., ; Pratto, Sidanius, & Levin, ) have received relatively less empirical attention within a system justification framework (but see Feygina & Tyler, ). By institutional level, we mean contributors to inequality that exist outside the heads of individuals and become manifested within the policies, procedures, practices, traditions, documents, and physical spaces of institutions.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, other disciplines have, in fact, begun to address how cultural expressions as well as other contextual factors strengthen the perceived association between African-Americans and crime. Social psychologists, political scientists, and economists have already shown how beliefs about the work ethic of African-Americans (e.g., Green, Staerkle, & Sears, 2006), attitudes about Black-sounding names (e.g., Bertrand & Mullainathan, 2004), and generalizations about physical spaces associated with African-Americans (e.g., Bonam, Taylor, & Yantis, 2017) may explain support for racially discriminatory policies and practices. For example, prior studies reveal that negative perceptions of African-American cultural values predict increased support for punitive criminal justice policies generally (Green et al, 2006) and, in particular, increase the perceived appropriateness of a drug search in a hypothetical scenario (Peffley, Hurwitz, & Sniderman, 1997).…”
Section: Reconceptualizing Anti-black Attitudesmentioning
confidence: 99%
“…For example, prior studies reveal that negative perceptions of African-American cultural values predict increased support for punitive criminal justice policies generally (Green et al, 2006) and, in particular, increase the perceived appropriateness of a drug search in a hypothetical scenario (Peffley, Hurwitz, & Sniderman, 1997). Relatedly, Bonam et al (2017) have demonstrated that, in addition to implicit bias and structural-level racism, the racialization of places has contributed to inadequate responses to public health crises and police brutality. In other words, the mental images of "Black spaces" are relevant to our understanding of a range of present-day racial disparities (e.g., Bonam et al, 2017;Correll, Wittenbrink, Park, Judd, & Goyle, 2011).…”
Section: Reconceptualizing Anti-black Attitudesmentioning
confidence: 99%
See 1 more Smart Citation